A Study of labor market condition on the Banladesh readymade garment industry - Hoque, Ahmed Anisul (KDI School, 2001)
The Readymade Garment (RMG) Industry is the most successful event in the economic history of Bangladesh. It is the single biggest multi-billion-dollar export earning industry; it is the nontraditional exporting industry with the greatest prospect for labor-using growth. At present, over seventy five percent of the total export earnings is from the RMG industry, and it employs near to 1.6 million of people of which about ninety percent are women. As the industry recruits, available, unskilled, semiskilled, and little educated workforce, the wage payments to the workers are lower, sometimes below the minimum wage. This wage cost advantage is the most significant factor of the RMG industry expansion in the economy. But the labor productivity is very low like wages; in fact, it is comparable with any other South Asian country. Unfortunately, the owners not only exploit the workers paying low wages, but also provide poor quality of working conditions, medical, leaves, and other facilities. On the other hand, there are so many uneven problems and challenges, like political instability, bureaucratic corruption, poor backward linkage industries, etc., to affect the comparative advantage of the industry in producing garments. Thus this paper will investigate the contribution of the RMG industry as the employer of large population, as well as the conditions of those working people. If the present trend of growth and expansion of the industry remains ongoing, then it can be expected that the Bangladesh economy have a great chance to get rid of the curse of poverty. But if the existing problems and the upcoming challenges can not be faced proficiently, the economy will have to face serious difficulty and growth will remain stand still.
Thesis(Master) --KDI School:Master of Public Policy,2001